The fauna of sciarid flies from the Dominican Republic (Diptera: Sciaridae). - Mohrig, Werner; Röschmann, Frank; Rulik, Bjoern (Contributions to Entomology = Beiträge zur Entomologie, 2004)
This report is the first comprehensive study on sciarids within the Caribbean fauna, which includes 50 species belonging to 11 genera, 44 of them new to science. Forty five species were collected in the Dominican Republic, five in Puerto Rico. The species belong to the following genera: Leptosciarella (2), Pseudosciara (4, two of them previously known), Chaetosciara (1), Cratyna (1), Hyperlasion (2, one of them previously known), Pseudolycoriella (13), Bradysia (16, one of them previously known), Scatopsciara (5), Corynoptera (2), Keilbachia (1) and Epidapus (3, one of them previously known).Assessing the Caribbean fauna is handicapped by lack of information on sciarids from neighboring mainland’s, especially Florida and South America. Nevertheless, due to thorough knowledge of the sciarid fauna of the Palaearctic Region and partial knowledge of that of the Nearctic Region and Central America, we can say that Caribbean sciarids show great similarities to Holarctic faunistic elements. This is particularly true for Leptosciarella, Chaetosciara, Keilbachia, Scatopsciara, most species of Bradysia, Corynoptera and Epidapus, and at least partly also for Pseudolycoriella. The only endemic Neotropical genus is Pseudosciara with four described species, and the two species of the Bradysia pararufescens group.KeywordsSciaridae, Dominican Republic, Puerto Rico, new species, taxonomy, Leptosciarella, Pseudosciara, Cratyna, Chaetosciara, Pseudolycoriella, Bradysia, Scatopsciara, Corynoptera, Keilbachia, Epidapus.Nomenclatural Actsacerba Mohrig & Röschmann, 2004 (Bradysia), spec. n.cauta Mohrig & Röschmann, 2004 (Bradysia), spec. n.ciliocera Mohrig & Röschmann, 2004 (Bradysia), spec. n.clara Mohrig & Röschmann, 2004 (Bradysia), spec. n.crassicera Mohrig & Röschmann, 2004 (Bradysia), spec. n.longioculosa Mohrig & Röschmann, 2004 (Bradysia), spec. n.mellea Mohrig & Röschmann, 2004 (Bradysia), spec. n.obtusa Mohrig & Röschmann, 2004 (Bradysia), spec. n.oculosa Mohrig & Röschmann, 2004 (Bradysia), spec. n.pararufescens Mohrig & Röschmann, 2004 (Bradysia), spec. n.reticulata Mohrig & Röschmann, 2004 (Bradysia), spec. n.spinea Mohrig & Röschmann, 2004 (Bradysia), spec. n.subspinea Mohrig & Röschmann, 2004 (Bradysia), spec. n.turgida Mohrig & Röschmann, 2004 (Bradysia), spec. n.gilva Mohrig & Röschmann, 2004 (Chaetosciara), spec. n.sicca Mohrig & Röschmann, 2004 (Corynoptera), spec. n.turbata Mohrig & Röschmann, 2004 (Corynoptera), spec. n.fumoalata Mohrig & Röschmann, 2004 (Cratyna (Cratyna)), spec. n.flavothoracicus Mohrig & Röschmann, 2004 (Epidapus (Epidapus)), spec. n.obstinatus Mohrig & Röschmann, 2004 (Epidapus (Pseudoaptanogyna)), spec. n.multisetus Mohrig & Röschmann, 2004 (Hyperlasion), spec. n.paucipalpa Mohrig & Röschmann, 2004 (Keilbachia), spec. n.nudinervosa Mohrig & Röschmann, 2004 (Leptosciarella (Leptosciarella)), spec. n.ampullocera Mohrig & Röschmann, 2004 (Leptosciarella (Protosciarella)), spec. n.aculeacera Mohrig & Rulik, 2004 (Pseudolycoriella), spec. n.barbata Mohrig & Rulik, 2004 (Pseudolycoriella), spec. n.curvimedia Mohrig & Rulik, 2004 (Pseudolycoriella), spec. n.florentissima Mohrig & Rulik, 2004 (Pseudolycoriella), spec. n.fuscivenosa Mohrig & Rulik, 2004 (Pseudolycoriella), spec. n.indocera Mohrig & Rulik, 2004 (Pseudolycoriella), spec. n.ovistyla Mohrig & Rulik, 2004 (Pseudolycoriella), spec. n.pulla Mohrig & Rulik, 2004 (Pseudolycoriella), spec. n.rotundostyla Mohrig & Rulik, 2004 (Pseudolycoriella), spec. n.subovistyla Mohrig & Rulik, 2004 (Pseudolycoriella), spec. n.torva Mohrig & Rulik, 2004 (Pseudolycoriella), spec. n.virgata Mohrig & Rulik, 2004 (Pseudolycoriella), spec. n.fragistyla Mohrig & Röschmann, 2004 (Pseudosciara), spec. n.longicera Mohrig & Röschmann, 2004 (Pseudosciara), spec. n.ventosa Mohrig & Röschmann, 2004 (Scatopsciara (Scatopsciara)), spec. n.abiecta Mohrig & Röschmann, 2004 (Scatopsciara (Xenopygina)), spec. n.caribiana Mohrig & Röschmann, 2004 (Scatopsciara (Xenopygina)), spec. n.destituta Mohrig & Röschmann, 2004 (Scatopsciara (Xenopygina)), spec. n.terribilis Mohrig & Röschmann, 2004 (Scatopsciara (Xenopygina)), spec. n.